2016
DOI: 10.3390/app6110373
|View full text |Cite
|
Sign up to set email alerts
|

The Machining of Hard Mold Steel by Ultrasonic Assisted End Milling

Abstract: Abstract:This study describes the use of ultrasonic-assisted end milling to improve the quality of the machined surface of hard Stavax (modified AISI 420) mold steel and to reduce the amount of work involved in the final polishing process. The effects of input voltage, the stretch length and cutter holding force on the amplitude of the ultrasonic vibration used were measured. The effect of ultrasonic frequency (25 and 50 kHz) and amplitude (0, 2.20 and 3.68 µm) as well as the effect of the rake angle (6 • and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Three values of rake angle (α) were proposed: 10 • , 20 • and 30 • . It is assumed that higher rake angles lead to lower cutting forces, so the selection of a positive rake angles [38,39] is recommended. However, there are some drawbacks for excessive rake angles.…”
Section: Selection Of Rake Angle (α) and Land Width (A)mentioning
confidence: 99%
“…Three values of rake angle (α) were proposed: 10 • , 20 • and 30 • . It is assumed that higher rake angles lead to lower cutting forces, so the selection of a positive rake angles [38,39] is recommended. However, there are some drawbacks for excessive rake angles.…”
Section: Selection Of Rake Angle (α) and Land Width (A)mentioning
confidence: 99%
“…Ding et al [83] found that feed per tooth has a significant effect on the height of the top burr, and the use of vibration-assisted cutting in micro end milling could minimize the size effect and improve the cutting performance, thereby reducing the height of the top burr by 80%. Tsai et al [84] investigated the machining of hard mold steel by ultrasonic assisted end milling, and found that a positive rake angle and a large helix angle gave improved surface finish. Maurotto and Wickramarachchi [85] investigated the effects of frequency in ultrasonically assisted end milling on grain sizes of AISI 316L.…”
Section: End Millingmentioning
confidence: 99%
“…As an intermittent cutting method, ultrasonic vibration machining (UAM) has been widely discussed for its ability to open the tool-workpiece contact area intermittently. As one of the typical UAM processes, the ultrasonic-assisted milling technique has been widely applied to machine difficult-to-cut alloys for its superiority in expanding tool life, lowering cutting force and delivering better surface quality [18][19][20][21][22][23][24]. In order to obtain the intermittent cutting mode between the tool and the workpiece in UAM, its relative velocity in cutting direction should be controlled as the opposite to the tool rotation direction periodically.…”
Section: Introductionmentioning
confidence: 99%